2007
DOI: 10.1159/000104712
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Morphology in Patients with Restless Legs Syndrome

Abstract: Aim: The aim of the study was to assess the cellular and structural properties of skeletal muscle in restless legs syndrome (RLS). Method: Twenty patients and 16 controls were included. Aerobic performance was assessed using a submaximal test. On muscle biopsies taken from the tibialis anterior, fiber distribution and fiber area were analyzed together with parameters surveying the microvascularization, especially the tortuosity, which is expressed as a percent of muscle fiber perimeter in contact with the wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…These could represent a sequelae of a general iron regulation problem. 26,27 Some recent studies have suggested an increased difference between morning and evening blood flow 28 and relative hypoxia in leg muscles of RLS/WED patients. 29 It may be that hypoxia or hypoxic pathway activation is one pathway to RLS/WED symptoms.…”
Section: Consequences Of Iron Deficiency: Hypoxic Pathway Activation mentioning
confidence: 99%
“…These could represent a sequelae of a general iron regulation problem. 26,27 Some recent studies have suggested an increased difference between morning and evening blood flow 28 and relative hypoxia in leg muscles of RLS/WED patients. 29 It may be that hypoxia or hypoxic pathway activation is one pathway to RLS/WED symptoms.…”
Section: Consequences Of Iron Deficiency: Hypoxic Pathway Activation mentioning
confidence: 99%
“…Wahlin-Larsson et al (32) studied the morphology of the skeletal muscle in patients with RLS and showed an increased microvessel tortuosity in these individuals. The authors proposed that the disturbance of the balance between vascoconstriction and vasodilation may be responsible for the emergence of the symptoms and that re-establishment of this balance through the movements of the extremity may provide symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…spinal cord transection, hind-limb suspension, spaceflight and sleep deprivation) neuromuscular activity [20,21,22]. Studies have shown that slow oxidative fibers demonstrate fundamental changes in physiological properties (markedly increased fatigue and altered rates of contraction and relaxation [23]) and are particularly sensitive to decreases in neuromuscular activity, as they are otherwise the most active [24]. Dupont-Versteegden et al [25] have established that adaptations in the expression of the MHC isoforms begin as early as 5 days after spinal cord transection.…”
Section: Discussionmentioning
confidence: 99%